Economic Evaluation of Belt and Road based on Bayesian risk perspective - Zhu, Tianxing; Zhao, Jianya; Zeng, Sicong; Xue, Liangzheng; Chen, Xuhan (Transactions on Economics, Business and Management Research, 2024)
The Belt and Road strategy covers a wide range of international cooperation and infrastructure construction, and it is of great significance to conduct economic evaluation. Based on the macroeconomic data and related indices of the countries along the Belt and Road from 2005 to 2023, this research evaluates the economic performance through general factor analysis and assesses the risk using Bayesian time-varying iterative model. It is found that the industrial production capacity and service level of the countries along the Belt and Road are in the middle and lower reaches, agricultural import and export capacity needs to be improved, and the risk coefficient shows a trend of increasing and then flattening, the risk uncertainty of the Maritime Silk Road index is the smallest, the risk uncertainty of the trade volume indices is higher, and the export uncertainty is higher than that of the import uncertainty. Finally, this research puts forward policy recommendations based on the empirical result.